Professional COM applications with ATL - Li, Sing (Wrox press ltd., 1998)
This book examines how and why you should use COM, ActiveX controls and DNA Business Objects, and how these components are linked together to form robust, flexible and scalable applications. A key part of the book is the extended case study in which we produce a distributed events calendar that fits Microsoft's Distributed interNet Applications (DNA) model. This three-tier application uses flexible browser-based controls for the client user interface, business objects on both client and server to process the required information efficiently and Universal Data Access to perform the queries and updates. It depends on the support for component-based development now available for Windows NT server.